Gerakan Literasi Bagi Pelajar Melalui “Tantangan Membaca” di Tali Jaranan Jakarta Timur - Rialdo Rezeky M. L. Toruan; Muhammad Saifulloh; Nanang Djamaluddin (Universitas Prof. Dr. Moestopo (Beragama), 2022)
Literacy is the ability to use information and knowledge to increase intelligence according to changes. Government programs must collaborate with various parties other than schools that formally and non-formally carry out literacy, community groups, both non-governmental organizations, communities and other elements of society. Each contributes according to their abilities and capacities. One method that is being tried as a response to the findings in various studies that have been carried out related to literacy in Indonesia is to carry out Community Service in the form of discussions and knowledge dissemination entitled